Cari hesap sözleşmesi - Murat, Burçak (My University, 2008)
CARİ HESAP SÖZLEŞMESİ (ÖZET) Uygulamada sıkça kullanılan cari hesap sözleşmesi bankacılık alanında da geniş bir kitle tarafından kullanılmaya başlanmıştır. Cari sözlük anlamı ile “yürüyen”, hesap kelimesi ise bir “muhasebe işlemi” olarak ifade edilir. Cari hesap, hukuki açıdan bir sözleşme iken, muhasebe açısından bir hesaplaşma türüdür. Cari hesap sözleşmesi Türk Ticaret Kanunun 87-99 maddelerinde düzenlenmiştir. 87. maddede, cari hesap iki tarafın karşılıklı alacak ve borçlarını istemekten vazgeçip, bir hesaba aktif ve pasif şeklinde aktararak sözleşme süresi sonunda ortaya çıkan bakiyeyi isteyebileceklerine dair bir anlaşma olarak tanımlanmıştır. Bu sözleşmenin tarafı herkes olabilir. Tacirler arasında yapılması şart değildir. Ayrıca bu sözleşme ancak yazılı şekilde yapılabilir. Cari hesap uygulamada karşımıza alacaklı ve borçlu cari hesap şeklinde çıkmaktadır. Alacaklı cari hesap, her zaman müşteri lehine alacak bakiyesi verirler. Bir tür mevduat hesabı niteliği taşımaktadırlar. Borçlu cari hesap, bankanın müşterisine tahsis ettiği kredinin çalışması için açılan hesaplardır. Borçlu cari hesaplar açık borçlu cari hesap veya teminatlı borçlu cari hesap şeklinde açılabilir. Banka kredi sözleşmelerinin cari hesap sözleşmesi niteliği taşıyıp taşımadığı tartışmalıdır. Yargıtay bu sözleşmelerin cari hesap sözleşmesi sayılmadığını ifade etmektedir. Bu sözleşmenin konusu alacak ve borçlardır ve tarafların birbirinden olan bütün alacakları kanunen mümkün olmak koşuluyla cari hesaba geçirilebilir. Ancak takas edilemeyen ve belli bir yöne harcanmak ve emre hazır tutulmak üzere teslim olunan para ve mallardan doğan alacaklar cari hesaba geçirilemez. Sözleşmeden önce doğan alacaklar da ancak tarafların anlaşması ile hesaba geçirilir. Cari hesaba geçirilen alacaklar sözleşme süresinin sonuna kadar tek başlarına talep ve dava edilemezler ve haczedilemezler. Fakat sözleşme süresi sonunda taraflarca tutulan bakiye tespit edilir. Karşı tarafa gönderilir. Karşı taraf bakiyeye bir ay içerisinde itiraz etmezse bakiyeyi kabul etmiş sayılır. Bu aşamadan sonra alacaklı bakiye talep edilebilir. CURRENT ACCOUNT CONTRACT (

) Current Account Contract, used very often in practice, has begun to be commonly used by the masses in banking. “Current” means “running” literally; “account” is meant by “accounting transaction.” While Current Account is a contract in terms of law, it is a kind of settlement in terms of accounting. Current Account Contract is regulated in the 87th-99th clauses of Turkish Commercial Code. In the 87th clause, Current Account is described as a contract by which the parties abandon their wills to ask for their reciprocal debit and credit entries, and they can demand the balance deriving from the closure of the contract, transferring it into an account as assets and liabilities. Everyone can be a party of this contract. It is not essential for this contract to be made between traders. Furthermore, this contract shall be concluded in writing. Current Account appears to be passbook savings and debit current account in practice. Credit current account always gives cash balance in favor of customers. It holds the distinction of being a savings account. Debit current account is the one which is opened for the running of the credit allocated by the banks to their customers. Debit current accounts can be opened in two ways. One of them is charge account, and the other is the one with secured debt. It is questionable whether credit contracts of the banks holds the characteristics of a current account contract. Supreme Court of Appeals states that these contracts cannot be regarded as a current account contract. The subject of this contract is debits and credit entries, and all credit entries between the parties can be transferred to the current account on condition that it is relevant in law. However, the credit entries that cannot be swapped and arise from the money and goods delivered for spending for a specific direction and keeping disposable cannot be entered into the current account. The credit entries having arisen before the contract can be put to the account under the conditions of the agreement between the parties. The credit entries that are entered into the current account cannot be demanded and sued alone, and cannot be arrested. However, the balance, held by the parties at the end of the contract period, is determined. It is sent to the other party. Unless the other party appeals against the balance, he shall serve to accept the balance. The creditor hereafter can demand the balance.
Keywords: Bankalar ve Bankacılık_Hukuk; Tİcaret Hukuku